Perinatal Care in Canada - Chalmers Beverley; Wen Shi (BMC Women's Health, 2004)
Abstract Health Issue Canada's standard of perinatal care ranks among the highest in the world, but there is still room for improvement, both in terms of regional differences in care and global comparisons of approaches to care in Canada and elsewhere. Data from the Canadian Perinatal Surveillance System (CPSS) was used to evaluate morbidity and mortality among mothers and infants. Key Findings Maternal mortality rates in Canada dropped to 4.4 per 100,000 live births in 1993–1997 and are among the lowest in the world. Rates of Caesarean section increased from 15.3 per 100 deliveries in 1994 to 19.1 in 1997. Although the infant mortality rate in Canada is among the lowest in the world (5.3–8.8 per 1,000 live births 1990–2000), there are unacceptable disparities between subpopulations. In Aboriginal populations, rates of stillbirth and perinatal mortality are 2–2.5 times the Canadian average. There has been a steady increase in the proportion of births among older women who have the highest risk of preterm births and pregnancy complications. The increasing rate of multiple births has accelerated recently and is of concern as these carry a higher risk of complications and are associated with an increased risk of preterm birth. The costs to the health care system are likely to be high. Data Gaps and Recommendations CPSS data, including economic indicators, needs to be collected in a more timely and uniform manner across Canada. The CPSS should provide an evaluation of how well Canada fares in relation to international standards of perinatal care.